Deregulated angiogenesis in chronic lung diseases: a possible role for lung mesenchymal progenitor cells (2017 Grover Conference Series). (December 2017) - Kropski, Jonathan A.; Richmond, Bradley W.; Gaskill, Christa F.; Foronjy, Robert F.; Majka, Susan M.
Chronic lung disease (CLD), including pulmonary fibrosis (PF) and chronic obstructive pulmonary disease (COPD), is the fourth leading cause of mortality worldwide. Both are debilitating pathologies that impede overall tissue function. A common co-morbidity in CLD is vasculopathy, characterized by deregulated angiogenesis, remodeling, and loss of microvessels. This substantially worsens prognosis and limits survival, with most current therapeutic strategies being largely palliative. The relevance of angiogenesis, both capillary and lymph, to the pathophysiology of CLD has not been resolved as conflicting evidence depicts angiogenesis as both reparative or pathologic. Therefore, we must begin to understand and model the underlying pathobiology of pulmonary vascular deregulation, alone and in response to injury induced disease, to define cell interactions necessary to maintain normal function and promote repair. Capillary and lymphangiogenesis are deregulated in both PF and COPD, although the mechanisms by which they co-regulate and underlie early pathogenesis of disease are unknown. The cell-specific mechanisms that regulate lung vascular homeostasis, repair, and remodeling represent a significant gap in knowledge, which presents an opportunity to develop targeted therapies. We have shown that that ABCG2 pos multipotent adult mesenchymal stem or progenitor cells (MPC) influence the function of the capillary microvasculature as well as lymphangiogenesis. A balance of both is required for normal tissue homeostasis and repair. Our current models suggest that when lymph and capillary angiogenesis are out of balance, the non-equivalence appears to support the progression of disease and tissue remodeling. The angiogenic regulatory mechanisms underlying CLD likely impact other interstitial lung diseases, tuberous sclerosis, and lymphangioleiomyomatosis.